Determinant of gross regional domestic product (GRDP) in Yogyakarta special province - Nur Feriyanto (Universitas Islam Indonesia, 2014)
The aim of this study is to analyze the influence of employment, investment and the number of tourists towards GRDP in Yogyakarta. The data used in this research is a time series data for the period of 1999-2013. This research employed multiple regression and dynamic regression, namely partial adjustment model. The multiple regression estimation shows that employment has negative effect to GRDP, meanwhile the investment and the number of tourists have a positive relation towards dependent variable. Moreover, based on partial adjustment model, adjustment process also influences the output accumulation in Yogyakarta. Therefore, to develop the local economy, the government may invite more tourists as well as increase investment in Yogyakarta.